Does Delta Hemoglobin-Albumin-Lymphocyte Platelet (HALP) Score Predict the Risk of Early Progression in Patients Treated with CDK4/6 Inhibitors? - Burcu Belen GÜLBAĞCI (Namık Kemal Tıp Dergisi, 2024)
Aim: This study aims to determine the predictive value of dynamic change in hemoglobin-albumin-lymphocyte-platelet (HALP) score on treatment response in hormone-positive metastatic breast cancer patients receiving cyclin-dependent kinase (CDK) 4/6 inhibitors. Materials and Methods: This study was designed retrospectively. Between January 1, 2020, and September 30, 2023, 104 patients diagnosed with metastatic hormone receptor-positive/human epidermal growth factor 2 receptor negative breast cancer were treated with CDK4/6 inhibitors plus endocrine therapies at Sakarya University Training and Research Hospital. Patients were divided into two groups according to whether there was progression at the initial response evaluation. Factors that could predict treatment response between the two groups were compared with regression analysis. Results: The median HALP score in patients was 34.08 (23.46-45.08) before treatment and 28.3 (19.24-42.61) at first response evaluation. Delta HALP was ≤0 for sixty-four (61.5%) patients, >0 for 40 patients (38.5%). There was no statistical difference in delta HALP score between groups with and without progression at the first response evaluation (p=0.334). The presence of liver metastasis and treatment line significantly affect the early progression by univariate and multivariate regression analysis (p=0.031 and p=0.016, respectively). Conclusion: Our study has found that the delta HALP score does not predict early progression. The presence of liver metastasis and later treatment line were found to be statistically significant with early progression. These data are compatible with the literature.